PENETAPAN KADAR NITRIT (NO2-) DALAM BAYAM MERAH DAN BAYAM HIJAU DENGAN METODE SPEKTROFOTOMETRI VISIBEL - Emma Emawati; Anne Yuliantini; Yusiana Yusiana (Fakultas Farmasi UMI, 2019)
Green and red spinach is a vegetable that has a lot of nutritional content and is needed by the body. Besides containing many nutrients that are beneficial to the body, spinach vegetables also contain compounds that are toxic, can harm the body such as nitrite (NO2-) and cause methemoglobinemia. The purpose of this study was to analyze the levels of nitrites in green and red spinach with a visible spectrophotometric method and to determine whether the nitrites contained were still within safe limits of consumption in accordance with the ADI (Acceptable Daily Intake) value. Before the content analysis, a validation method was conducted with parameters including linearity with r = 0.9994, BD = 0.0499 µg / mL, BK = 0.1664 µg / mL,% recovery of day 1 = 1.5597 to 2 = 1.7547, the 3rd = 1.0126 and accuracy at a concentration of 0.3 μg / mL = 88.800%, 0.5 μg / mL = 95.332% and 0.7 μg / mL = 107.410%. Nitrite levels in fresh green spinach obtained an average of 23.4084 mg / kg, and 12.7272 mg / kg in red spinach. Furthermore, the green spinach after boiling yields an average of 16.8392 mg / kg and red spinach was 5.3359 mg / kg. Nitrite levels from all green and red spinach samples are still within safe limits for consumption in accordance with the ADI (Acceptable Daily Intake) value of 0.07 mg / kg of a predetermined human body weight.